Let's go fishing - Slade, Suzanne (New York : PowerKids Press, 2007)
An introduction to the sport of fishing, discussing where people fish, the gear and bait they use, fishing techniques, and the different types of fishing and fish.
The sport of fishing -- Where to fish -- Fishing gear -- Bait -- Casting a line -- Freshwater fishing -- Fishing in the ocean -- Fly-fishing -- Ice fishing -- Kinds of fish -- Fishing and nature -- Let's go fishing.
Includes index.
4.9
3-6
Keywords: Fishing -- Juvenile literature; Fishing; Fishing; Fishing